APLIKASI SISTEM SELEKSI CALON KARYAWAN PT. DATACOM SOLUSINDO - Noviyanti, Retno; Retnoningsih, Dwi; Al Haris, Firdhaus Hari Saputro (JURNAL GAUNG INFORMATIKA, 2018)
Company as an organization that is driven by human resources faced with a variety of selection in order to determine a quality workforce. The success of a company can not be separated from the role of employees as Human Resources (HR),  which runs the activities to promote the company in question.The choices made by a company in the recruitment of new employees is very influential on the performance and progress of the company, so the company must be careful in selecting new candidates. Decision-making involving many alternatives and many of the criteria is certainly not an easy thing, it will take a lot of time and a great opportunity errors occur. It is based because the screening directly handled by the manager so that the manager is sometimes difficult to divide his time.  Based on these problems, PT. Datacom Solusindo requires Selection of Prospective Employees Systems in order to assess new candidates. The research objective is to build an application System Selection of Prospective Employees are expected to help PT. Datacom Solusindo in selecting new candidates. The methods used in researchare the waterfall method, profile matching and black box waterfall method, profile matching method and black box method.The result of research is that new system is able to provide the calculation result in accordance with manual result and is able to provide on rangking candidates from the most recommended based on calculation of weighted value of prospective employees. The test results on the Admin is logged, the post of managing data, manage the data of prospective employees, prospective employees manage profile data, personnel data management, doing the counting process, and report test results to the user that is logged in and view reports on ranking all work well.